2018
DOI: 10.1017/s1754470x18000156
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapted Family Intervention (CaFI): case examples from therapists’ perspectives

Abstract: This paper describes three case examples from a recent trial of family intervention specifically designed for people of African-Caribbean descent. These examples, told from the therapists’ perspectives, highlight key components of the intervention and issues that arose in working with this client group. Findings from the study suggest that it is possible to engage this client-group in family therapy similar to traditional evidenced-based family interventions, although as illustrated in the paper, it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Despite this constraint, family-based intervention was still recommended by all included studies because of its cited effectiveness in individual studies, primarily in symptom reduction and improved family dynamics. A majority of the studies also reported decreased relapse rate, consistent with the evidence from HICs [ 33 , 53 , 83 ]. Additionally, patient outcomes related to decreased EE [ 20 , 22 , 84 ] that have been observed in HICs were also evident in the LMICs.…”
Section: Discussionsupporting
confidence: 78%
“…Despite this constraint, family-based intervention was still recommended by all included studies because of its cited effectiveness in individual studies, primarily in symptom reduction and improved family dynamics. A majority of the studies also reported decreased relapse rate, consistent with the evidence from HICs [ 33 , 53 , 83 ]. Additionally, patient outcomes related to decreased EE [ 20 , 22 , 84 ] that have been observed in HICs were also evident in the LMICs.…”
Section: Discussionsupporting
confidence: 78%
“…(b) Cultural adaptation of therapies for a diverse population Culturally adapted Family Intervention (CaFI): case examples from therapists' perspectives (Berry et al, 2018) These authors pioneered cultural adaptation of a CBT-based family intervention for psychosis for African-Caribbean people in England, and found it to be feasible and acceptable (Edge et al, 2018a,b). This paper reports on the process of culturally adapted family intervention from a therapist's perspective.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…There is (a) one systematic review of CBT for social anxiety among the culturally diverse population (Jankowska, 2019). There are (b) seven articles covering different aspects of adaptation of therapies for diverse populations which include: culturally adapted family intervention using case studies (Berry et al , 2018), a discussion of maladaptive schema and schema therapy in the context of Greek culture (Kolonia et al , 2019), use of a transdiagnostic intervention in low resource countries (Murray et al , 2019), application of acceptance and commitment therapy (ACT) with a Turkish population in London (Perry et al , 2019), a framework to culturally adapt CBT (Rathod et al , 2019), a case report of family-based CBT for obsessive compulsive disorder (OCD) from Saudi Arabia (Alatiq and Alrshoud, 2018) and a paper discussing CBT in military culture (Zwiebach et al , 2019). Three papers (c) address the issues of gender and sexuality.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Case study examples found the therapists were able to include all these components and successfully engage the African-Caribbean service users in FI (Berry et al, 2018). Furthermore, therapists were able to do this in the absence of biological family members and the FSM were viewed as an effective alternative (Berry et al, 2018).…”
Section: Interventionmentioning
confidence: 99%
“…(1) Engagement and Assessment (focused around building trust with mental health professionals), (2) Shared Learning (addressed illness beliefs and explanatory models), (3) Communication (aided family members and service users in speaking with each other and to health professionals), (4) Problem-Solving and Stress Management (geared at helping families to better manage stressors to reduce tension), and (5) Maintaining Gains and Staying Well (developed a crisis plan to attempt to reduce pathways into care involving police). Case study examples found the therapists were able to include all these components and successfully engage the African-Caribbean service users in FI (Berry et al, 2018). Furthermore, therapists were able to do this in the absence of biological family members and the FSM were viewed as an effective alternative (Berry et al, 2018).…”
Section: Interventionmentioning
confidence: 99%